Peranan Pemuridan dalam Membangun Disiplin Rohani Menurut 2 Timotius 2:2 dan Implementasinya Bagi Jemaat Masa Kini - Baskoro, Paulus Kunto; Pattinama, David; Budiono, Endah Totok; Batubara, Riston (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2022)
Discipleship is an important part of the Person of the Lord Jesus, as long as he is on earth. Jesus has an important purpose in coming to this world, shich is to atone for the sins of manking and provide restoration of life for humans who should go to hell, when they believe in the Lord Jesus, they can enjoy heaven. But Jesus did not escape a discipleship that was carried out with the twelve disciples He had chosen. Jesus took a discipleship seriously for three and a half years. The church must also consistently carry out discipleship. Because through discipleship, spiritual discipline will accur effectively. Because it in undeniable, when the church is separated from the discipleship system, it will lose many generations and the church growth will be ineffective. The book of 2 Timothy 2:2 becomes an important text to explore the principle of discipleship that leads to spiritual discipline. The method used a descriptive method of literature. Thus research will discuss about effective ways of evangelism, so that evangelism is more effective and can be applied in all ages. The purpose of thus paper is First, to explain how important discipleship is. Second, examine the important prinsiples of discipleship fot the spiritual discipline of the church based on 2 Timothy 2:2. Third, apply the right discipleship system that can have an impact on today’s congregations.AbstrakPemuridan menjadi bagian penting dari Pribadi Tuhan Yesus, selama ada di dunia. Yesus memiliki tujuan penting datang ke dunia yaitu menebus dosa umat manusia dan memberikan pemulihan kehidupan untuk manusia yang seharusnya masuk neraka, ketika percaya kepaada Tuhan Yesus, bisa menikmati sorga. Namun Yesus tidak lepas dengan sebuah pemuridan yang dilaksanakan dengan duabelas murid yang telah dipilih-Nya. Yesus menerapkan pemuridan dengan serius selama tiga setengah tahun. Gereja seharus juga secara konsisten untuk melaksanakan pemuridan. Sebab melewati pemuridan, maka disiplin rohani akan terjadi secara efektif. Sebab tidak bisa dipungkiri, ketika gereja lepas dari sistem pemuridan maka akan kehilangan banyak generasi dan pertumbuhan gereja tidak efektif. Kitab 2 Timotius 2:2 menjadi nast penting untuk mengupas prinsip pemuridan yang membawa kepada disiplin rohani.Metode yang digunakan adalah metode deskriptif literatur. Penelitian ini akan membahas tentang cara yang efektif dalam penginjilan, sehingga penginjilan lebih tepat guna dan dapat diaplikasikan dalam segala zaman. Tujuan dalam penulisan ini adalah Pertama, menjelaskan betapa pentingnya pemuridan. Kedua, mengkaji prinsip-prinsip penting dalam pemuridan bagi disiplin rohani jemaat berdasarkan 2 Timotius 2:2. Ketiga, menerapkan secara tepat sistem pemuridan yang bisa membawa dampak bagi jemaat masa kini.